2008
DOI: 10.1063/1.3043587
|View full text |Cite
|
Sign up to set email alerts
|

Deformation behavior of an amorphous Cu64.5Zr35.5 alloy: A combined computer simulation and experimental study

Abstract: Molecular dynamics ͑MD͒ simulations were performed to examine the temperature-dependent elastic properties and high-temperature deformation behavior of a Cu 64.5 Zr 35.5 amorphous alloy. From the simulations we find that the elastic constants of the amorphous solid and supercooled liquid exhibit an approximately linear temperature dependence. The predicted temperature dependence of the Young's modulus for the amorphous solid obtained from the MD simulations is in good agreement with experimental measurements u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 37 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Glass transition occurs when G decreases to 85% of the shear modulus at 0 K, that is, G (T g ) =0.85 G (0 K) [15]. Mendelev et al [18] showed that G does not decrease to zero in a flash, but has a quick reduced transition region. Moreover, this region does not crystallize.…”
Section: Discussionmentioning
confidence: 98%
“…Glass transition occurs when G decreases to 85% of the shear modulus at 0 K, that is, G (T g ) =0.85 G (0 K) [15]. Mendelev et al [18] showed that G does not decrease to zero in a flash, but has a quick reduced transition region. Moreover, this region does not crystallize.…”
Section: Discussionmentioning
confidence: 98%
“…To reduce these effects, we utilized a biaxial deformation geometry in this work. The deformation was carried out at T=300 K. A compressive strain in the x-and y-directions was applied at a constant strain rate of 2.0×10 7 s -1 , which is typical order of magnitude used in MD simulations [25,26,41]. The model was deformed until the final strain of ε xx =ε yy = -0.2 (ε zz ≈0.53).…”
Section: B Details Of Deformationmentioning
confidence: 99%
“…MD simulation was performed with the LAMMPS package [19] for Cu 50 Zr 50 metallic glass with a realistic embeddedatom method potential [20]. The sample containing 96 000 atoms in a cuboid with period boundary conditions (PBCs) was first fully equilibrated at 2000 K for 1 ns, then quenched down to 50 K with the cooling rate of 1 K/ps in isothermal-isobaric (N -P -T ) ensemble.…”
Section: Model and Methodsmentioning
confidence: 99%